DIVERSITY AND ACADEMIC ACHIEVEMENT IN SECONDARY EDUCATION: IMPLICATIONS FOR INCLUSIVE PRACTICES - Bennett, Oliver; Walker, Ethan; Martin, Lucas; Clarke, Benjamin; Wilson, Henry (International Journal For Research In Educational Studies, 2024)
This study explores the relationship between socio-demographic factors and academic achievement in high school,focusing on generalizing conclusions on inclusive instructional practices. The research design adopted was thequantitative research design because it was based on the secondary data of 1000 students on Kaggle. The analysis wasdone in Python and the following statistics were applied to evaluate the influence of gender, race/ethnicity, parentaleducation, socio-economic status, and test preparation on academic achievement: descriptive statistics, groupcomparison, correlations analysis, and multiple linear regression. These findings suggest that socio-demographic factorshave a significant relationship with academic performance. The female studentsperformed better in overall performance,and the males in mathematics. The socio-economic status and the preparation of tests proved to be good predictors andstudents who had higher socio-economic status and had undergone preparatory courses performed better. The level ofparental education also positively correlated with performance in school. Its results indicate the necessity of equal accessto educational opportunities and specific support measures to cope with differences. These lessons can be used to shapepolicies to support inclusive education. The study adds to the literature by using secondary data to indirectly measureinclusion based on performance gaps, which has practical implications to enhance equity in secondary education.